Chest Pain Management Using Prehospital Point-of-Care Troponin and Paramedic Risk Assessment (Medical Forum Monthly, 2024)
Objective: To evaluate the prehospital point-of-care troponin testing and paramedic risk stratification withinexisting chest pain care pathways reveals promising reliability and validity, suggesting their potential as valuabletools in enhancing early cardiac assessment and improving patient outcomes.Study Design: Prospective studyPlace and Duration of Study: This study was conducted at the Department of Medicine, Nishtar MedicalUniversity, Multan, from February 2021 to January 2022.Methods: Study included 400 consecutive patients experiencing acute chest pain categorized as emergencies. Allpatients were transported to the hospital via ambulance for subsequent medical care. Positive TnT test prehospitaland at the time of hospital admission were compared. Main variables of study were values of troponin test inmyocardial infarction associated chest pain patients at hospital and during emergency travelling and previous historycoronary artery disease, myocardial infarction and risk factors like diabetes, smoking and hypertension.Results: Myocardial infarction was positive in 32.0% in chest pain patients. Prehospital troponin was positive in 33(8.3%) patients. Troponin test was positive in 53.8% patients at admission. The sensitivity for prehospital troponinto myocardial infarction was 18.0% and the sensitivity to myocardial infarction for in-hospital troponin was 74.2%with specificity 96.3% and 55.9%, respectively. (p<0.001).Conclusion: In regions where patient transport times are brief, the point-of-care rapid Troponin T (TnT) test revealsonly a minority of individuals experiencing chest associated, prehospital TnT test positive outcome emerges as anobjective indicator for a more adverse prognosis in those with suspected heart attacks.